Penerapan Metode MOORA dan ROC Dalam Pemilihan Oli Mesin Terbaik Untuk Sepeda Motor Matic - Serdina Feria Sidabutar; Rima Tamara Aldisa; Geofani Pasaribu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
As the use of automatic type of motorbike vehicles increases, the problem also increases in the automotive world because there are many users of automatic type motorcycle vehicles who do not understand how to care for and maintain the durability of their automatic motorbikes, especially the most important part of the motorbike, namely the the engine components. Machine maintenance is inseparable from lubricating oil which has a function in lubricating engine components so that they are maintained, durable, & away from rusting or even chipping because of friction between components one with another which results in damage to the motorbike engine so that their favorite motorbike has to be make repairs to the workshop. Moreover, the motorbike used is of the automatic type, where maintenance is much more complicated than other motorbikes, which are of the gear or clutch type. In determining the best engine oil for the best automatic motorbikes, starting from the contents of the package which are at least 1 liter, has a non-concentrated odor, and is able to keep the engine cool when the motorbike is used. Combination of the MOORA and ROC Methods in the selection of the best engine oil for the best automatic type motorcycle based on predetermined criteria for the “Evalube” brand alternative S5 oil with a preference value of 0.019 as the best engine lubricating oil for automatic type motorcycles. The application of the MOORA Method has a simple and easy-to-understand concept in selecting the best engine oil for automatic type motorcycles. The process of selecting the best engine oil for automatic type motorbikes using the MOORA and ROC methods, starts from determining the weight value of each criterion and then ranking the largest preference value as a consideration and aid in decision making.